IMPLEMENTASI PERMENHUB NOMOR 18 TAHUN 2021 TENTANG PENGAWASAN ANGKUTAN BARANG (STUDI KASUS WILAYAH SIDOARJO) - Islammudin, Mukhammad; Mardijono, H. R.Adianto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This article aims to describe and describe the implementation of supervision of the Motorized Vehicle Weighing Unit in Trosobo Sidoarjo regarding goods transport vehicles which in practice are in accordance with the Law, namely PERMENHUB number 18 of 2021. In addition, the purpose of this research is to get an overview of challenges faced in the field regarding the implementation of supervision of goods transport in Sidoarjo. The author in this study uses a type of empirical juridical research. This type of research produces results in the form of descriptive data such as speech, writing to the behavior of the research subjects. The subjects of this study were drivers of goods transport vehicles and supervisory staff of the Trosobo Motor Vehicle Weighing Unit. Data collection techniques used by the authors are interviews, literature studies, documentation, and observation. The findings of this study indicate that the Trosobo Motorized Vehicle Weighing Unit (UPPKB) has carried out its duties well, even though there were obstacles encountered in the implementation, such as a lack of supervisory personnel, less than optimal supporting facilities and a lack of solid synergy with stakeholders and other parties. involved in the handling of motorized vehicle control